Independent Curriculum Development Strategy in Islamic Religious Education: Conceptual Studies of Building Character and Nationality - Nurdiyanto Nurdiyanto; Ahmad Musyfiq; Karman Karman; Asep Nursobah (Tarbiyah: Jurnal Ilmiah Kependidikan)
This research aims to develop a unique curriculum for Islamic Religious Education (Pendidikan Agama Islam/PAI) and how to build character and nationality in students in an independent curriculum. The approach used in this research is qualitative, using library research methods. The data collection technique in this research is collecting from the sources mentioned, classifying the data, and continuing with the conclusion. The data analysis technique uses descriptive analysis. The results of this research show that there are several strategies for developing the Islamic religious education curriculum in building national character and insight, including Discovery Learning (DL), Inquiry Learning (IL), Problem-Based Learning (PBL), Project Based Learning (PJBL), and Scientific Learning (SL). So, there is a second alternative to carrying out this learning by using learning methods that focus on how students work in understanding, analyzing, and practicing. The implication of this research is that curriculum development and students' national attitudes is the foundation for the learning process using contemporary methods.